DEVELOPMENT OF A PROMOTIONAL WEBSITE TO INCREASE ENTREPRENEURIAL INTEREST IN VOCATIONAL HIGH SCHOOL STUDENTS - Lika Jafnihirda; Ganefri -; Asmar Yulastri (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The background of this research is that there are many students in the Craft Production Design Vocational School who are able to produce usable products such as cabinets, chairs, souvenirs and other household appliances, but it turns out that the products produced by students are not put to good use. on display in the school gallery and there are some products that students take home because they are only used for school work. This research method uses Research and Development (R & D) with Borg and Gall research and development procedures which consist of six stages, research and information gathering, planning, product development, field trials and product revisions, final product revisions and dissemination. Based on the research and development that has been done, a website is produced. The results obtained from this study are website-based product promotion media and student expertise that are valid and effective for increasing interest in entrepreneurship